ANALISIS PENGARUH CONSUMER PRICE INDEX DAN PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI ASIA TIMUR DAN PASIFIK - Khairunnisa, Nabila (LPPM Universitas Bina Bangsa, 2024)
This study aims to analyze the factors influencing economic growth in East Asia and the Pacific. The data used was taken in 2012-2022. A multiple linear regression model with the development of a model using the Ordinary Least Square (OLS) method was used to analyze the relationship between economic growth and independent variables such as the consumer price index (CPI) and education. The results of the study show that all independent variables have a positive and significant influence on the dependent variable, namely economic growth